Sustained visual acuity loss in the comparison of age-related macular degeneration treatments trials - Ying, Gui-shuang; Kim, Benjamin J; Maguire, Maureen G; Huang, Jiayan; Daniel, Ebenezer; Jaffe, Glenn J; Grunwald, Juan E; Blinder, Kevin J; Flaxel, Christina J; Rahhal, Firas; Regillo, Carl; Martin, Daniel F (JAMA ophthalmology, 2014)
Although anti-vascular endothelial growth factor treatment of neovascular age-related macular degeneration (AMD) results in improved vision overall, loss of substantial vision can occur. Understanding the processes that lead to loss of vision may lead to preventive strategies. To determine the incidence, characteristics, causes, and baseline predictors of sustained visual acuity loss after 2 years of treatment with ranibizumab or bevacizumab for neovascular AMD. A cohort study within a randomized clinical trial of participants in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). Participants were randomly assigned to treatment with ranibizumab or bevacizumab and to 2 years of monthly or as needed injections or monthly injections for 1 year and as needed injections the following year. Sustained visual acuity loss, defined as loss of 15 or more letters from baseline at weeks 88 and 104. Among 1030 participants, 61 eyes (5.9%) developed sustained visual acuity loss in 2 years. Within this group, visual acuity decreased gradually over time, with a mean decrease of 2, 19, and 33 letters from baseline at 4 weeks, 1 year, and 2 years, respectively. At 2 years, eyes with sustained visual acuity loss had more scarring (60.0% vs 41.4%, P = .007), more geographic atrophy (GA) (31.6% vs 20.7%, P = .004), larger lesions (16 vs 8 mm2, P < .001), and higher proportions of intraretinal fluid (82.5% vs 51.0%, P < .001), subretinal hyperreflective material (84.5% vs 44.2%, P < .001), retinal thinning (43.3% vs 23.0%, P < .001), and thickening (20.0% vs 12.1%, P < .001). Likely causes of sustained visual acuity loss included foveal scarring (44.3%), pigmentary abnormalities (27.9%), and foveal GA (11.5%). Baseline factors independently associated with a higher incidence of sustained visual acuity loss were the presence of nonfoveal GA (odds ratio [OR],  2.86; 95% CI, 1.35-6.08; P = .006), larger area of choroidal neovascularization (OR for a >4-disc area vs ≤1-disc area, 3.91; 95% CI, 1.70-9.03; P = .007), and bevacizumab treatment (OR,  1.83; 95% CI, 1.07-3.14; P = .03). Sustained visual acuity loss was relatively rare in CATT. The development of foveal scar, pigmentary abnormalities, or GA contributed to most of the sustained visual acuity loss. Risk was 3% higher among eyes treated with bevacizumab. Treatment that targeted the prevention of scarring or GA may improve vision outcomes. clinicaltrials.gov Identifier: NCT00593450.